Analisis Kemandirian Belajar Siswa Dalam Pembelajaran Daring Di Kelas III SDN Dayeuhluhur CBM - Mila Rahayu; Din Azwar Uswatun; Andi Nurochmah (STKIP Andi Matappa Pangkep, 2020)
This study aims to describe the independence of student learning and inhibiting factors in online learning in grade III SDN Dayeuhluhur CBM. This study use the descriptive qualitative research methods. The subject used in this study were the teacher and representatives of class III students. Data collection techniques in this study used interviews and documentation. Data analysis techniques use the stages of data reduction, data presentation and conclusions or verification. The result of this study is the independence of student learning in online learning in grade III SDN Dayeuhluhur CBM is quite well developed although there are still some students who lack confidence, active, disciplined and responsible for learning. The inhibiting factors that cause students to not be independent in the online learning is the emergence of boredom because they do not interact directly with the teacher, limited handphones used in online learning and still using parents handphone, fast quota runs out, unstable network, parents who are busy working and students lack understanding of the material. Due to several inhibiting factors in online learning, teachers have difficulty determining assessment and only rely on attendance in task collection.